1992
DOI: 10.1161/01.hyp.19.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Diminished phospholipase C activation by dopamine in spontaneously hypertensive rats.

Abstract: It is reported that a defect in dopamine-1 (DA-1) receptor adenylate cyclase coupling in the proximal convoluted tubule in the spontaneously hypertensive rat may contribute to the diminished natriuretic response to DA-1 receptor agonists. Since the tubular DA-1 receptor is also coupled to phospholipase C, and both of these cellular signaling processes are involved in DA-1 receptor-mediated diuresis and natriuresis, it is important to know whether a similar defect is also present in DA-1 receptor-coupled phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…In conscious, as well as in anesthetized animals, up to 60% of sodium excretion during an acute volume load is mediated by D 1 receptors (7); this is due both to an increase in renal dopamine production and to an increased sensitivity of sodium transporters to dopaminergic inhibition (7,12). In the spontaneously hypertensive rat (SHR), 1 the ability of exogenous and endogenous renal dopamine to engender a natriuresis is impaired (13)(14)(15). Since renal dopamine levels in genetic models of hypertension are not lower than those found in their normotensive controls (16,17), the impaired intrarenal paracrine effect of dopamine in these animal models of hypertension appears to be receptor or postreceptor-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…In conscious, as well as in anesthetized animals, up to 60% of sodium excretion during an acute volume load is mediated by D 1 receptors (7); this is due both to an increase in renal dopamine production and to an increased sensitivity of sodium transporters to dopaminergic inhibition (7,12). In the spontaneously hypertensive rat (SHR), 1 the ability of exogenous and endogenous renal dopamine to engender a natriuresis is impaired (13)(14)(15). Since renal dopamine levels in genetic models of hypertension are not lower than those found in their normotensive controls (16,17), the impaired intrarenal paracrine effect of dopamine in these animal models of hypertension appears to be receptor or postreceptor-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, disruption of the D 1 receptor in mice produces hypertension (12, 13). The pivotal role of dopamine in the excretion of sodium after increased sodium intake has led to the hypothesis that an aberrant renal dopaminergic system is important in the pathogenesis of some forms of genetic hypertension (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Several mechanisms potentially responsible for the failure of endogenous renal dopamine to engender a natriuretic effect in genetic hypertension have been investigated and ruled out, including decreased renal dopamine production and receptor expression, aberrant nephron segment distribution of dopamine receptors, defective effector enzymes (adenylyl cyclase or phospholipase C), and abnormal renal sodium transporters (3,8,13,17).…”
mentioning
confidence: 99%
“…The paracrine͞ autocrine dopaminergic regulation of sodium excretion is mediated by tubular but not by hemodynamic mechanisms (6). The ability of dopamine and D 1 -like agonists to decrease renal proximal tubular sodium reabsorption is impaired in genetic rodent hypertension and human essential hypertension (3,5,(7)(8)(9)(10)(11)(12)(13)(14)(15). Indeed, the aberrant D 1 -like receptor function in the kidney precedes and cosegregates with high blood pressure in spontaneously hypertensive rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…62 Subsequently, studies from many laboratories have confirmed and extended these observations. [63][64][65][66][67][68][69] This defect is present in human proximal tubule cells and is confined to the proximal tubule. 53 Studies now are beginning to point toward a possible defect in D 1 receptor-G protein complex recycling and recruitment of receptors to the cell membrane.…”
Section: Careymentioning
confidence: 99%